Sense of coherence (SOC) versus health behaviour in nurses - Urbańska, Bogumiła; Kurowska, Krystyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2010)
Introduction : Sense of coherence (SOC) is a construct that explains the relationship between health behaviour and health. High SOC gives confidence in the meaning of life, its comprehensibility and predictability – which gives motivation to stay healthy and fit. The aim of the research was to define SOC level and health behaviour of nurses. Material and methods : 77 nurses from different wards: Pediatric Surgery, General Surgery Clinic, Gastroenterology Clinic, Vessel Diseases, Neurosurgery and Neurotraumatology at Dr Jan Biziel University Hospital No 2 in Bydgoszcz were examined. Sense of coherence was assessed on the basis of the SOC-29 questionnaire, while health behaviour on the basis of Health Behaviour Inventory. Results : Global SOC in nurses was 130 (92-167 points), with average level of understanding 51.24; manageability 42.54; meaningfulness 35.55 points. The result in Health Behaviour Inventory was 83.56 points. 33% of the examined nurses showed a low level in Health Behaviour Inventory, 44% were on medium level, and 25% showed a high level of health behavior. Conclusions : On the basis of the results we can conclude that nurses constitute the group of professionals with high SOC and appropriate or high level of health behaviour.